Barriers to tuberculosis drug discovery: the mycobacterial cell wall - Whittaker, Caitlin (Department of Pathology, 2023)
The mycobacterial cell wall is a highly complex macromolecular structure that provides intrinsic resistance to several anti-tuberculosis drugs, making it critical in the success of Mycobacterium tuberculosis infection. Multiple layers encapsulate the cell membrane, including arabinogalactan chains and mycolic acids that are covalently bonded to the peptidoglycan layer, resulting in a highly selectively permeable barrier that is unique to this genus. The current treatment for tuberculosis (TB) utilizes antibiotics that weaken the structural integrity of the cell wall to allow easier access for drugs that have intracellular targets. Although this approach is theoretically effective, patient adherence is often poor owing to the lengthy treatment times and negative side effects associated with the multidrug combination regimen. As such, rational drug design to develop more potent, faster-acting anti-TB compounds requires a comprehensive understanding of the composition and functioning of the mycobacterial cell envelope to ensure effective penetration through this barrier. Bioinformatic approaches to compound validation provide a crucial foundation for drug development, but empirical validation of these molecules can present a serious bottleneck in the drug discovery pipeline. Here, we investigated fluorescent click chemistry as a rapid and inexpensive means of ascertaining molecular properties that impact compound permeation of the mycobacterial cell envelope. The variability in permeation of different click-reactive moieties could be rapidly determined using fluorescent read-outs; this, in combination with the availability of a wide array of click-reactive side chains, presents a potentially powerful platform for establishing the properties required by a compound to effectively cross the mycomembrane. Enzymatic degradation of cell wall components further revealed the resilience of mycobacteria as the resulting organisms, spheroplasts, were capable of surviving in the absence of this seemingly essential protective layer. This presents a potentially novel form of intrinsic resistance whereby stripping of the cell wall could allow for tolerance to cell wall active antibiotics, a previously under-appreciated strategy that has been reported in other pathogenic bacteria. Together, these findings highlight the highly dynamic nature of the mycobacterial cell envelope and the need for further investigation into the properties of this structure that allow for such efficient antibiotic evasion.